Enhanced Microbial Utilization of Recalcitrant Cellulose by an Ex Vivo Cellulosome-Microbe Complex - You, Chun (American Society for Microbiology, 2012)
A cellulosome-microbe complex was assembled ex vivo on the surface of Bacillus subtilis displaying a miniscaffoldin that can bind with three dockerin-containing cellulase components: the endoglucanase Cel5, the processive endoglucanase Cel9, and the cellobiohydrolase Cel48. The hydrolysis performances of the synthetic cellulosome bound to living cells, the synthetic cellulosome, a noncomplexed cellulase mixture with the same catalytic components, and a commercial fungal enzyme mixture were investigated on low-accessibility recalcitrant Avicel and high-accessibility regenerated amorphous cellulose (RAC). The cell-bound cellulosome exhibited 4.5- and 2.3-fold-higher hydrolysis ability than cell-free cellulosome on Avicel and RAC, respectively. The cellulosome-microbe synergy was not completely explained by the removal of hydrolysis products from the bulk fermentation broth by free-living cells and appeared to be due to substrate channeling of long-chain hydrolysis products assimilated by the adjacent cells located in the boundary layer. Our results implied that long-chain hydrolysis products in the boundary layer may inhibit cellulosome activity to a greater extent than the short-chain products in bulk phase. The findings that cell-bound cellulosome expedited the microbial cellulose utilization rate by 2.3- to 4.5-fold would help in the development of better consolidated bioprocessing microorganisms (e.g., B. subtilis) that can hydrolyze recalcitrant cellulose rapidly at low secretory cellulase levels.